2003
DOI: 10.1021/jp027132u
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Calculation of Entropy and Heat Capacity of Gas-Phase n-Alkanes Using Internal Rotations

Abstract: This work attempts to improve the theoretical reproduction of thermodynamic properties, such as entropies and heat capacities of gas-phase n-alkanes, by using a more precise quantum-mechanical treatment of the internal rotations. Present ab initio methods all handle the internal modes in the harmonic oscillator approach. It has already been noted that this approach underestimates the microscopic partition functions (Van Speybroeck et al., J. Phys. Chem. A 2000, 104, 10939). In this work, an uncoupled scheme fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 20 publications
10
125
0
Order By: Relevance
“…To take thermochemical effects due to rotation of single bonds into consideration, the one-dimensional hindered rotor (1-D-HR) approach of Van Speybroeck and coworkers [38][39][40] is applied. It is well known that such a treatment significantly improves the calculated thermochemical properties, 39 in particular the entropy results.…”
Section: Hindered Rotor Treatmentmentioning
confidence: 99%
“…To take thermochemical effects due to rotation of single bonds into consideration, the one-dimensional hindered rotor (1-D-HR) approach of Van Speybroeck and coworkers [38][39][40] is applied. It is well known that such a treatment significantly improves the calculated thermochemical properties, 39 in particular the entropy results.…”
Section: Hindered Rotor Treatmentmentioning
confidence: 99%
“…This method is referred to as the onedimensional hindered rotor scheme (1D-HR). The procedure to calculate the internal rotor partition functions was already discussed in references [13,16] and we refer to these articles for further details. We only mention that a rotational potential is determined for each rotor m by fitting a Fourier expansion to the energies of the fully optimized stable conformers and rotational transition state structures [Eq.…”
Section: àEa=rt ð3þmentioning
confidence: 99%
“…Speybroeck also studied effects of coupling between internal rotors and report that the coupling has only, a minor influence on the kinetics, relative to treating all internal rotors as uncoupled. Speybroeck et al reported overall good agreement between experimental and calculated entropy and heat capacity values for n-alkanes, treating internal rotors without coupling [22]. Chen and Bozzelli [23] have also shown very good agreement between calculated and experimental o ( ) and ( ) for ethers and ether radicals when internal rotation contributions were included.…”
Section: Thermodynamic Propertiesmentioning
confidence: 88%